Elementary School Students' Poetry Writing Skills - Mariana; Slamet; Matsuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study was motivated by the low poetry writing skills of elementary school students, which can be seen from the lack of variation in diction, minimal use of language style, and limitations in expressing ideas creatively. The aim of this research is to analyze supporting aspects in writing poetry including theme, diction, imagination, rhyme, and amana. The method in this research uses a qualitative approach with an exploratory qualitative design. The research subjects consisted of 20 fifth grade students. Techniques for collecting data using documentation. The data analysis technique uses semantic analysis. The research results showed that the level of students' ability to write poetry in the theme aspect obtained an average percentage of 86.25% with a very good category and the dominant types of themes used were themes about parents, school, environment and friends. The diction aspect obtained an average percentage of 85% in the good category, the rhyme aspect obtained an average percentage of 60% in the sufficient category, the imagination aspect obtained an average percentage of 46.25% in the adequate category and the words used for imagination were sight, hearing, smell, and for the mandate aspect, the average percentage was 86.25% in the very good category. The conclusion of this research is that the ability to write poetry for class V students at SDN Wonogiri is in the good category with a percentage of 72.75%.